(untitled) (Quaderni di Gargnano, 2018)
The paper looks at letterbooks, namely collections of letters written in the vernacular, and considers the problems of attribution that arise when individual letters are anthologized in book form and therefore undergo formal changes. In particular, the paper explores the different gradations of authorship attributable to letters that have passed through the hands of several different professionals in their passage from personal archives into print. The paper focuses on the twenty-three epistolary sylloges published by Paolo Manuzio between 1542 and the 1564 in the three volumes titled Lettere volgari di diversi nobilissimi huomini, and seeks to distinguish between the authors, the publisher and the editor. The paper reviews the authorial status of letters that were directly collected, edited and published by scholars such as Paolo Manuzio or Curzio Troiano di Navò, printers such as Paolo Gherardo, and polygraphs such as Giovanni Antonio Clario, Lodovico Dolce and Dionigi Atanagi, and considers the extent to which the signatories of the letters could and did claim ownership of the texts.